2005
DOI: 10.1002/ejoc.200500111
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(I)‐Mediated Intramolecular [2+2+2] Cocyclizations of (Methylenecyclopropyl)diynes as an Easy Access to Cyclopropanated Oligocycles

Abstract: Enediynes with methylenecyclopropane moieties attached either through the three-membered ring or the double bond smoothly underwent cobalt-mediated [2+2+2] cocyclizations to give cyclopropane-fused and spirocyclopropanated cobaltcomplexed tricyclo[7.3.0.0 2,6 ]dodeca-1,6-dienes (1,2,3,3a,4, 6,7,8-octahydro-as-indacenes) under relatively mild conditions in yields ranging from 31 to 94 % (6 examples). Electron-withdrawing substituents at the acetylenic terminus of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Cobalt mediated an intramolecular [2 + 2 + 2]cycloaddition of methylenecyclopropyldiynes to give cyclopropanated polycycles [1289]. Cobalt mediated [2 + 2 + 2]cycloadditions were used to prepare aryl-containing macrocycles [1290], [7]helicenelike molecules [1291] and the deoxygenated pancrastistatin core [1292].…”
Section: Cycloadditionsmentioning
confidence: 99%
“…Cobalt mediated an intramolecular [2 + 2 + 2]cycloaddition of methylenecyclopropyldiynes to give cyclopropanated polycycles [1289]. Cobalt mediated [2 + 2 + 2]cycloadditions were used to prepare aryl-containing macrocycles [1290], [7]helicenelike molecules [1291] and the deoxygenated pancrastistatin core [1292].…”
Section: Cycloadditionsmentioning
confidence: 99%
“…203 Under Heck conditions, these processes produced in good yields (63e65%) the corresponding cross-conjugated trienes depicted in Scheme 132, which are substituted monocyclic [3]dendralenes. In addition, the same cross-conjugated trienes were isolated in good-to-excellent yields (79e92%) from the corresponding 1,6-and 1,7-enynes by a more economic, palladium-catalysed cycloisomerisation, as shown in Scheme 132.…”
Section: Heck Reactionsmentioning
confidence: 98%
“…130 Therefore, it was found that methylenecyclopropyldiynes bearing an electron-withdrawing substituent at the acetylenic terminus were suitable substrates for Co-mediated intramolecular [2þ2þ2] cocylisations to provide the corresponding cyclopropane-fused and spirocyclopropanated tricyclic skeletons in moderate-to-excellent yields as mixtures of diastereomers. As shown in Scheme 79, the process was performed upon irradiation in boiling THF in the presence of a stoichiometric amount of CpCo(CO) 2 .…”
Section: [2d2d2] Cycloadditionsmentioning
confidence: 99%
“…The [2+2+2] cycloaddition is not a reaction that is exclusive for triple bonds, as it can also take place between two acetylenes and one alkene giving rise to cyclohexadienes. Given this, the same concept could be applied for the completely intramolecular [2+2+2] cycloaddition of enediynes to afford fused polysubstituted cyclohexadienes (Equation 3, Scheme 1 ) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%